2′-F-ANA-guanosine and 2′-F-guanosine as powerful tools for structural manipulation of G-quadruplexes - Lech, Christopher Jacques (2013)
Here we demonstrate the applicability of 2′-F-ANA-guanosine and 2′-F-guanosine as powerful tools for manipulating G-quadruplex folding by anti-position-favoring substitutions. A single guanine to 2′-F-ANA-guanine substitution can favor a single (3+1) hybrid conformation from a mixture of conformers. Rational substitutions of either type of 2′-F-modified nucleotide enable conformational switching from a (3+1) hybrid to a parallel folding topology.